Cultivation of Cucumbers in Greenhouse Conditions: No Chemical Pollution - Eshkobilov, S. A; Abdikholikova, F N; Kuchkarova, D X; Khujamshukurov, N A (European Journal of Applied Sciences, 2023)
This article shows the importance of vermicompost when growing cucumbers in greenhouse conditions. In particular, it was noted that biohumus is significantly superior to traditional components widely used in seedling cultivation in terms of the amount of nutrients and other indicators. In the course of the research, the results of an agrochemical analysis of the initial soil mixture, the composition of manure and biohumus for the main nutrients before the start of the experiment were obtained: an average three-year increase in nutrients in the substrate (soil-wood shavings) indicators was revealed. The pH value is 7.08, the density of the mixture is 0.43 g/cm3. The smallest amount of nutrients (NPK) in mixtures by options (N-83.8 mg/l, NH4-9.9 mg/l, NO3-73.8 mg/l, P2O5-11.7 mg/l, K2O- 122.9 mg/l, MgO -21.8 mg/l, CaO-57.3 mg/l.) NH4-73.5 mg/l, NO3-532.6 mg/l). l, P2O5-61.3 mg/l, K2O-773.5 mg/l, MgO-84.7 mg/l, CaO-126.0 mg/l.) corresponds to the variant using 100% biohumus. The ratio of nutrients in this option is N-7.2, NH4 -7.4, NO3-7.2, P2O5 -5.2, respectively; K2O-6.3, MgO-3.9, CaO-2.2 were equal. According to different options, a change in the average density of the substrate in 2019-2021 was established. within 0.21-0.50 g/cm3, depending on the amount of applied biohumus. It shows that changing the amount of vermicompost in the substrate does not significantly affect the pH of the substrate. In this research work, the effect of biohumus on the agrochemical properties of the soil, fertility and productivity of cucumbers in greenhouse conditions is studied. Since biohumus stores a large amount of nutrients, when added to the soil, it changes the amount of nutrients in the soil. Since biohumus contains trace elements and humic acids, it has an effect of enhancing plant development in cucumber cultivation. Greenhouse soil treated with mineral fertilizer was used as a control option in the experiment. The amount of mineral fertilizer applied to the soil in different years was determined based on the level of nutrient supply of the greenhouse soil as a result of agrochemical analysis. For all options, the plant was fed with the specified amount of mineral and organic fertilizer every 30 days. Application of mineral fertilizers was carried out in two stages. The amount of mineral fertilizers calculated on the basis of the chemical analysis of the soil carried out in the first stage was added. In the second stage, a certain amount of organic fertilizer-biohumus was added according to different options. The mineral fertilizer used in feeding is the same in all options: nitrogen 29 mg/kg (or 7.5 g/m2), phosphorus (P2O5) 19.5 mg/kg (or 5.0 g/m2) and potassium (in terms of K2O) was equal to 23.5 mg/kg (or 6.0 g/m2). Mineral fertilizers were given in the form of ammonium nitrate (22.0 kg/ha), double superphosphate (25 kg/ha) and potassium chloride (11 kg/ha). Comparing the amount of NPK determined after feeding for each option with the amount of NPK before feeding in these options shows the increase in the amount of nutrients in 2019-2021: N-1.2-1.7; P-1.2-2.0; It shows that K–1.2-2.3 times. This mainly corresponded to options 5-8, where feeding with biohumus in the amount of 1.0 kg/m2 was carried out in several stages. According to option 5th, the amount of nitrogen in the soil increased from 50 mg/kg to 90 mg/kg, the amount of phosphorus from 53 mg/kg to 101 mg/kg, and the amount of potassium from 49 mg/kg to 66 mg/kg was observed in the 3rd year. In option 9th, where 4.0 kg/m2 of biohumus was used under the plow, at the end of the experiment, the amount of NPK in the soil of the experimental plot decreased from the optimum. At the end of the experiment, a significant decrease in NPK was observed in the soil of the site where manure was used at the rate of 2 kg/m2 for feeding. As a result of intensive use of the soil in greenhouse conditions, it was observed that the amount of mineral substances necessary for the development of the plant, especially micro- and macroelements in the mobile form, in the soil of the control option, where only mineral fertilizer was used, was significantly reduced. Usually, in such cases, it is required to use high-quality mineral fertilizers and other chemical compounds in order to obtain a high yield under closed soil conditions. As a result, an excess amount of harmful chemicals accumulates in the crop. The use of biohumus during feeding prevents such unpleasant situations. Nutrients in the 10th variant with a biohumus content of 90% are more than the number of nutrients in the 5th variant (40% biohumus content): nitrogen-2.13, phosphorus-1.96, potassium-2.06, magnesium-1.82 and Ca-1.45 times higher. A low rate for nitrogen was observed in the second year of the experiment, and for phosphorus and magnesium in the first year of the experiment. The highest level of potassium and calcium corresponded to the 3rd year of the experience (2021). It is noted that the values of these elements, determined by the composition of the substrate in the 1st-2nd years of the experiment, do not differ sharply from each other. According to the results of agrochemical analysis, the amount of nutrients in the substrate reaches optimal values in initial mixtures containing 30-50% biohumus. Thus, the dynamics of changes in the amount of nitrogen in the substrate when growing cucumber seedlings corresponds to a change in the amount of vermicompost in the mixture, the amount of vermicompost up to 50%, total nitrogen in the mobile form and its N-NH4, which is consumed at later stages of plant development, and the amount of N forms. -NO3 increases. In the following concentrations of vermicompost, the amount of useful nitrogen decreases with an increase in the next time from the day of sowing. The value of the total consumption of phosphorus and potassium in the substrate, corresponding to the period of full development of seedlings, is in the range of 8.0-14.7 mg/l for phosphorus and 45.0-136.1 mg/l for potassium. observed. The use of vermicompost when growing cucumber seedlings stabilizes the agrochemical parameters of the soil in greenhouse conditions, reduces the seedling maturation period, and increases the plant's resistance to fungal diseases. The influence of the amount of heavy metals in the mixture used for growing biohumus was also studied. In the control variant, prepared from a mixture of soil and wood chips in a 1:1 ratio with the use of mineral fertilizers, the mixture containing lead (6.11 mg/kg) and zinc (23.00 mg/kg) appears to be slightly contaminated. The soil is rich in cadmium (0.30 mg/kg) and copper (2.96 mg/kg) and poor in cobalt (0.50 mg/kg) and nickel (0.87 mg/kg), which corresponds to the gradation with average values.